Annual stalagmite-derived SSTs for Bermuda (1449-2013) - Forman, Edward C G; Baldini, J U L; Jamieson, Robert A; Lechleitner, Franziska A; Walczak, Izabela W; Nita, Dan C; Smith, Struan R; Richards, David A; Baldini, Lisa M; McIntyre, Cameron; Müller, Wolfgang; Peters, Andrew J (In: Forman, ECG et al. (2025): Magnesium-derived sea surface temperature reconstruction (1449 to 2013 CE) from a Bermudan stalagmite [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.987043, 2025)
Mean annual SSTs spanning the last ~564 years modelled from a calibration with a previously-published coral record. The confidence interval (95%) reflects purely the calibration uncertainty.
Keywords: magnesium; palaeoclimate reconstruction; Sea surface temperature; SST; stalagmite; stalagmites